Biomechanical Comparison of Panda Rope Bridge Technique and Other Minimally Invasive Achilles Tendon Repair Techniques In Vitro. Issue 6 (11th June 2021) - Wang, Ting; Mu, Yuan; Diao, Yulei; Liu, Wenke; Wu, Yahong; Wang, Zhuoqun; Luo, Yanfeng; Xie, Yangli; Yin, Liangjun
Background: Although nonoperative management of acute Achilles tendon rupture (ATR) is a reasonable option, surgical repair has attracted attention for young and active patients. More reliable Achilles tendon repair techniques are needed to enhance recovery after ATR in this population. Purpose/Hypothesis: To biomechanically analyze the panda rope bridge technique (PRBT) and compare it with other minimally invasive repair techniques over a simulated, progressive rehabilitation program. It was hypothesized that PRBT would result in better biomechanical properties and enhanced recovery after ATR. Study Design: Controlled laboratory study. Methods: An Achilles tendon rupture was created 4 cm from the distal tendon insertion site in 40 bovine lower extremities, and specimens were then randomly allocated to 5 Achilles tendon repair techniques: (1) Achillon, (2) modified Achillon, (3) Percutaneous Achilles Repair System (PARS), (4) modified PARS, and (5) PRBT. Each group was subjected to a cyclic loading protocol that was representative of progressive postoperative rehabilitation for ATR (250 cycles at 1 Hz for each loading stage: 20-100 N, 20-200 N, 20-300 N, and 20-400 N). Results: The PRBT technique demonstrated significantly less elongation (1.62 ± 0.25 mm) than the 4 other repair techniques after the first loading stage of 20 to 100 N ( P < .05). All specimens in the 4 other groups developed a large gap (elongation ≥5 mm) at the 20- to 200-N loading stage. When overall biomechanical performance was examined, the PRBT group exhibited higher strength (20-400 N) and more mean loading cycles (984 ± 10) compared with the 4 other groups ( P < .05). Conclusion: In this bovine model, PRBT biomechanically outperformed the other minimally invasive Achilles tendon repair techniques that were tested and could therefore meet the requirements of accelerated rehabilitation. Clinical Relevance: The reduced tendency for premature rerupture and the overall improved biomechanical properties of PRBT suggest that ATR patients treated with PRBT may more readily complete early and aggressive postoperative rehabilitation protocols. In addition, they may have a lower risk of early irreversible suture failure.